Bibliometrik Analysis and Systematic Review of Trends in Dietary Patterns and Nutritional Intervention for Stunting Prevention - Indah Muthia Ayuni; Kasmita Kasmita; Anni Faridah (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
This study aims to analyze the trends, patterns, and thematic developments of scientific publications related to dietary patterns, stunting prevention, and nutritional interventions using a bibliometric approach with Biblioshiny and VOSviewer, as well as the PRISMA method within the ScienceDirect database. This research employs a Systematic Literature Review (SLR) method, covering publications from 2001 to 2025. Through the stages of identification, screening, eligibility assessment, and inclusion, a total of 32 scientific articles met the final criteria.The results indicate a significant increase in the number of publications in recent years, reflecting growing global attention to stunting prevention through nutritional interventions. Bibliometric analysis reveals that balanced dietary patterns have become a central theme in nutritional intervention strategies, particularly in programs aimed at improving children's nutritional status. The most frequently cited studies highlight the effectiveness of community-based interventions, supplementation of macro- and micronutrients such as Lipid-based Nutrient Supplements (LNS), and the role of policies and global initiatives such as Scaling Up Nutrition (SUN). The research network mapping shows the formation of major thematic clusters focusing on community-based nutrition interventions, evaluation of global nutrition policies, and integrative approaches to stunting prevention.These findings provide comprehensive insights into the direction and key contributions of research in the field of nutrition and serve as a reference for academics and health practitioners in designing evidence-based interventions and policies. Practically, these findings underscore the important role of the culinary field in translating balanced dietary concepts into locally based menu planning through recipe modification, food fortification, and culinary-based nutrition education. Thus, nutritional interventions are not only conceptual but also applicable and contextual within community life.